Avaliação da importância de habitats secundários para a manutenção de abelhas silvestres em áreas agrícolas - Montagnana, Paula Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The greatest threats to bees populations is the changing in the land use, mainly the actions related to agricultural intensification. It is necessary to have whitin the farms places that provide different kinds of resources to the different bees species for their conservation in those areas. The present study featured the bee community in four farms of conventional farming and family management in Guapiara (SP) about food specialty, substrate for nesting, sociability and total body size. Through the pollen on the bees body ruderal species plants and crops visited by them were identified, and through the network ecology approach bee-plant interactions were studied. Specimens catch were made once a month by two collectors on farms, from 8 am to 1 pm, for one year, a total of 50 hours/farm. It was identified 64 bees species, where Apidae was the richest and abundant family (565 specimens and 31 species), followed by Halictidae, Andrenidae, Megachilidae and Colletidae. About 85% of the bees species had specimens with body size smaller than 11,5 mm, about 39% of the bees species were solitary. Virtually all species were poliletic and more than 76% of the bees species nested in the soil. It was found 104 pollen types, from which 38 were identified until species, genus or family and 66 morphotypes were grouped in the category “others”. The pollen types identified belonging to ruderal plants were the most frequent on the samples, both during the wet and hot season and the dry and cold one. Lycopersicon esculentum pollen type was the most frequent (127 times) on the samples, followed by Asteraceae pollen type (111 times), Leonurus sibiricus (95 times), Poaceae (71 times) and Sonchus oleraceus (70 times). Generally, we can say that the bee-plant networks are fragile and somewhat resistant to withdrawal of the most abundant plant species. Ruderal plants were very important to the bee community, especially Leonurus sibiricus, Asteraceae and...

As maiores ameaças às populações de abelhas estão relacionadas às alterações no uso e ocupação do solo, principalmente as ações relacionadas a intensificação agrícola. A existência dentro das propriedades agrícola de locais que supram as necessidades das diferentes espécies de abelhas é essencial para a manutenção e a conservação desses animais em área agrícolas. O presente estudo procurou caracterizar as comunidades de abelhas presente em quatro propriedades rurais de cultivo convencional e manejo familiar no município de Guapiara (SP) com relação a especialidade alimentar, substrato utilizado para a nidificação, sociabilidade e tamanho total do corpo. Através de análise dos grãos de pólen aderidos aos corpos das abelhas, foram identificadas as espécies de plantas ruderais e cultivadas visitadas pelas mesmas, e através da abordagem de redes mutualísticas, foram estudadas as interações abelha-planta. As coletas dos espécimes de abelhas foram realizadas uma vez por mês com dois coletores por propriedade, das 8 horas às 13 horas, ao longo de um ano, totalizando 50 horas de coleta/propriedade. Foram identificadas 64 espécies de abelhas, sendo Apidade a família mais rica e abundante (565 espécimes e 31 espécies), seguida por Halictidae, Andrenidae, Megachilidae e Colletidae. Aproximadamente 85% das espécies de abelhas tiveram indivíduos com tamanhos corporais menor que 11,5 mm, cerca de 39% das espécies foram solitárias e praticamente todas as espécies foram poliléticas, com mais de 76% das espécies nidificando no solo. Com relação às amostras de pólen analisadas, foram encontrados 104 tipos polínicos, sendo 38 identificados até espécie, gênero ou família e 66 morfotipos, agrupados na categoria outros. Os tipos polínicos das plantas ruderais foram os mais frequentes dentro das amostras, tanto durante o período chuvoso e quente quanto no seco e frio. O tipo polínico mais encontrado foi...
Keywords: Bees; Abelha; Polinização por abelhas; Habitat (Ecologia); Interação animal-planta; Guapiara (SP)